Monitoring the impact of COVID-19 in Myanmar: Rice millers - September 2020 survey round - Goeb, Joseph; Zone, Phoo Pye; Synt, Nang Lun Kham; Cho, Ame; Tang, Yulu (International Food Policy Research Institute, 2020)
This is the third policy note in a series presenting the results from rounds of telephone surveys with rice millers in three important rice-growing regions of Myanmar: Ayeyarwady, Bago, and Yangon. Mills are the most important link between farms and consumers in the rice value chain. Thus, any shocks to rice mills will impact both rural rice-producing households as well as urban consumers.